Nanoelectrical and Nanoelectrochemical Imaging of Pt/p‐Si and Pt/p+‐Si Electrodes. Issue 22 (7th August 2017) - Jiang, Jingjing; Huang, Zhuangqun; Xiang, Chengxiang; Poddar, Rakesh; Lewerenz, Hans‐Joachim; Papadantonakis, Kimberly M.; Lewis, Nathan S.; Brunschwig, Bruce S.
Abstract: The interfacial properties of electrolessly deposited Pt nanoparticles (Pt‐NPs) on p‐Si and p + ‐Si electrodes were investigated on the nanometer scale using a combination of scanning probe methods. Atomic force microscopy (AFM) showed highly dispersed Pt‐NPs with diameters of 20–150 nm on the Si surface. Conductive AFM measurements showed that only approximately half of the particles exhibited measurable contact currents, with a factor of 10 3 difference in current observed between particles at a given bias. Local current–voltage measurements revealed a rectifying junction with a resistance ≥10 MΩ at the Pt‐NP/p‐Si interface, whereas the Pt‐NP/p + ‐Si samples formed an ohmic junction with a local resistance ≥1 MΩ. The particles were strongly attached to the sample surface in air. However, in an electrolyte, the adhesion of the particles to the surface was substantially lower, and most of the particles had tip‐contact currents that varied by a factor of approximately 10. Scanning electrochemical microscopy (SECM) showed smaller but more uniform electrochemical currents for the particles relative to the currents observed by conductive AFM. In accord with the conductive AFM measurements, the SECM measurements showed conductance through the substrate for only a minority of the particles. These results suggest that the electrochemical performance of the electrolessly deposited Pt nanoparticles on Si can be ascribed to: 1) The high resistance of the contact between the particles and the substrate, 2) the low (<50 %) fraction of particles that support high currents, and 3) the low adhesion of the particles to the surface when in contact with the electrolyte. Abstract : About electrons and electrical contact : The interfaces between electrolessly deposited Pt nanoparticles and p‐type Si are investigated by atomic force microscopy (AFM to reveal the topographical, electrical, and mechanical properties. Only half of the nanoparticles show electrical contact with the Si substrate, and adhesion of the nanoparticle to the Si is much weaker in electrolyte than in air.